2000
DOI: 10.1097/00004872-200018090-00020
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure responses to high-calcium skim milk and potassium-enriched high-calcium skim milk

Abstract: High-calcium milk enriched with potassium has a small hypotensive effect in healthy people aged over 40 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Although saturated fat intakes remained marginally higher than the recommended maximum of 10% energy from saturated fat, there was no evidence of a blood-pressure-lowering effect of milk supplementation even after adjusting for dietary factors. Therefore, although our results contrast with several short-term intervention studies in both normotensive (Van Beresteijn et al, 1990;Buonopane et al, 1992;Hilary Green et al, 2000) and hypertensive individuals (Hilary Green et al, 2000), they are consistent with the results from a meta-analysis indicating that increasing dietary calcium has a negligible effect on lowering blood pressure (Dickinson et al, 2006). An unexpected finding in our study was the significant (3.9-6.8 mm Hg) increase in SBP and DBP in both groups after 2 years.…”
Section: Discussionsupporting
confidence: 87%
“…Although saturated fat intakes remained marginally higher than the recommended maximum of 10% energy from saturated fat, there was no evidence of a blood-pressure-lowering effect of milk supplementation even after adjusting for dietary factors. Therefore, although our results contrast with several short-term intervention studies in both normotensive (Van Beresteijn et al, 1990;Buonopane et al, 1992;Hilary Green et al, 2000) and hypertensive individuals (Hilary Green et al, 2000), they are consistent with the results from a meta-analysis indicating that increasing dietary calcium has a negligible effect on lowering blood pressure (Dickinson et al, 2006). An unexpected finding in our study was the significant (3.9-6.8 mm Hg) increase in SBP and DBP in both groups after 2 years.…”
Section: Discussionsupporting
confidence: 87%
“…From the 31 remaining studies, nine were not retained as they did not include the necessary quantitative information, or the eligibility of published results could not be assessed. In another study, relative changes in SBP between intervention and placebo arms were not available [18]. Six additional studies were excluded as recruited participants were under antihypertensive medication during the trial.…”
Section: Search Resultsmentioning
confidence: 99%
“…Earlier feeding studies have shown that supplementation of usual diet with dairy products may reduce BP. [25][26][27] In the DASH trial, a combination diet that was rich in fruits and vegetables and low-fat dairy products with low saturated and total fat reduced SBP and DBP by 5.5 and 3.0 mm Hg more, respectively, compared to the control diet, whereas the corresponding BP reduction were 2.8 and 1.1 mm Hg more for the fruits and vegetables diet alone. 11 A more profound BP reduction with the addition of 2 servings/d of low-fat dairy products, along with other aspects of the combination diet, was observed both in subjects with hypertension and in those without hypertension.…”
Section: Wang Et Al Dairy Intake and Hypertensionmentioning
confidence: 99%